TI_GERICHTE 90.2007.28 vom 14. März 2008 , Approvazione di un comprensorio edificato fuori dalle zone edificabili - TI Tribunale d'appello (2008)
Approvazione di un comprensorio edificato fuori dalle zone edificabili